HLA Preferences for Conserved Epitopes: A Potential Mechanism for Hepatitis C Clearance - Rao, Xiangyu; Hoof, Ilka; van Baarle, Debbie; Keşmir, Can; Textor, Johannes (Frontiers in Immunology, 2015)
Hepatitis C virus (HCV) infections affect more than 170 million people worldwide. Most of these individuals are chronically infected, but some clear the infection rapidly. Host factors seem to play a key role in HCV clearance, among them the human leukocyte antigen (HLA) class I molecules. Certain HLA molecules, e.g. B*27 and B*57, are associated with viral clearance. To identify potential mechanisms for these associations, we assess epitope distribution differences between HLA molecules using experimentally verified and in silico predicted HCV epitopes. Specifically, we show that the NS5B protein harbors the largest fraction of conserved regions among all HCV proteins, which could be good targets for cytotoxic T cell (CTL) responses. We find that the protective HLA-B*27 molecule preferentially presents cytotoxic T cell (CTL) epitopes from NS5B, and in general presents the most strongly conserved epitopes among the 23 HLA molecules analyzed. In contrast, HLA molecules known to be associated with HCV persistence do not have similar preferences, and appear to target the variable P7 protein. Overall, our analysis suggests that by targeting highly constrained - and thereby conserved - regions of HCV, the protective HLA molecule HLA-B*27 reduces the ability of HCV to escape the cytotoxic T cell response of the host. For visualizing the distribution of both experimentally verified and predicted epitopes across the HCV genome, we created the HCV epitope browser, which is available at theory.bio.uu.nl/ucqi/hcv.